1984
DOI: 10.1136/bmj.289.6453.1179
|View full text |Cite
|
Sign up to set email alerts
|

Screening for small for dates fetuses: a controlled trial.

Abstract: In the hope of reducing perinatal risks associated with retardation of intrauterine growth a previously described two stage ultrasound screening schedule was evaluated by a controlled trial in 877 women with low risk single pregnancies. The two stages of ultrasound examination were an assessment of gestational age during early pregnancy followed by measurement of length from crown to rump and area of trunk at between 34 and 36 weeks' gestation. The product of crown to rump length and trunk area was calculated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
3
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(55 citation statements)
references
References 20 publications
1
49
3
2
Order By: Relevance
“…In one trial, no significant difference was found between the Apgar scores for the two groups 328 Ringa/Carrat/Blondel/Breart Misdiagnosis of IUGR and Preterm Elective Cesarean Section [10]; however, the series only included 33 SFD babies (17 in the routine group and 16 in the selective group). In the other trial, 2 peri natal deaths due to IUGR were reported in the scanned group versus four in the con trol group [11], Furthermore, Hughey [6], who conducted a nonrandomized controlled study, did not observe any significant differ ence in the outcome for the SFD babies be tween the routinely and selectively scanned groups.…”
Section: Discussionmentioning
confidence: 99%
“…In one trial, no significant difference was found between the Apgar scores for the two groups 328 Ringa/Carrat/Blondel/Breart Misdiagnosis of IUGR and Preterm Elective Cesarean Section [10]; however, the series only included 33 SFD babies (17 in the routine group and 16 in the selective group). In the other trial, 2 peri natal deaths due to IUGR were reported in the scanned group versus four in the con trol group [11], Furthermore, Hughey [6], who conducted a nonrandomized controlled study, did not observe any significant differ ence in the outcome for the SFD babies be tween the routinely and selectively scanned groups.…”
Section: Discussionmentioning
confidence: 99%
“…Neilson et al [ 18] compared correctly diagnosed and non-diagnosed small-for-date babies, but their series were too small (16 versus 17) to enable them to show really significant differ ences. We are now examining the conse quences of erroneous diagnosis in a further analysis of the population studied here.…”
Section: Discussionmentioning
confidence: 99%
“…In 1984, the focus of the Glasgow study [12] was to detect infants who were small for dates. The authors found a sensitivity and specificity of 94 and 90%, respectively, for identified infants who were small for dates.…”
Section: Early Experience With Routine Screening Ultrasound Policiesmentioning
confidence: 99%
“…It is important for the clinician to realize [12], 1984 877 24 and 32 no improvement no reduction of induced labor Aselund study [13], 1984 1,628 18 reduction of induced labor Trondheim study [14], 1984 1,009 19 and 32 no improvement that comprehensive examination of the fetal anatomy is an essential, not optional, part of the routine examination. Screening may lead to unnecessary anxiety if there is a false-positive result, or to a false sense of security if there is a false-negative result [5].…”
Section: Introductionmentioning
confidence: 99%